2012
DOI: 10.1146/annurev-neuro-062111-150525
|View full text |Cite
|
Sign up to set email alerts
|

The Attention System of the Human Brain: 20 Years After

Abstract: Here, we update our 1990 Annual Review of Neuroscience article, “The Attention System of the Human Brain.” The framework presented in the original article has helped to integrate behavioral, systems, cellular, and molecular approaches to common problems in attention research. Our framework has been both elaborated and expanded in subsequent years. Research on orienting and executive functions has supported the addition of new networks of brain regions. Developmental studies have shown important changes in cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

101
2,449
8
74

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 2,732 publications
(2,632 citation statements)
references
References 84 publications
101
2,449
8
74
Order By: Relevance
“…A striking finding was that the overlap between the TIS and the cognitive DSA included a sizeable cluster that localized to the medial frontal cortex, a structure that has been implicated in problem solving (Bush, Luu, & Posner, 2000) and attention (Petersen & Posner, 2012; Posner & Petersen, 1990) and is known to be activated during arithmetic strategy selection (Taillan et al., 2015) and the counting Stroop test (Bush et al., 1998). In fact, one study reported that patients with focal injury (either infarction, hemorrhage, trauma, or resection of a benign tumor) in the medial frontal cortex had difficulty counting the numbers in a series of auditory stimuli (Shallice, Stuss, Alexander, Picton, & Derkzen, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A striking finding was that the overlap between the TIS and the cognitive DSA included a sizeable cluster that localized to the medial frontal cortex, a structure that has been implicated in problem solving (Bush, Luu, & Posner, 2000) and attention (Petersen & Posner, 2012; Posner & Petersen, 1990) and is known to be activated during arithmetic strategy selection (Taillan et al., 2015) and the counting Stroop test (Bush et al., 1998). In fact, one study reported that patients with focal injury (either infarction, hemorrhage, trauma, or resection of a benign tumor) in the medial frontal cortex had difficulty counting the numbers in a series of auditory stimuli (Shallice, Stuss, Alexander, Picton, & Derkzen, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As absurd as this example sounds, comparable situations often proceed unnoticed in the domain of cognition. Parents might avoid demanding the impossible of their children if they knew of Michael Posner's work on the development of attentional networks 41 , which suggests that young infants can orient (direct attention) to a new item, but may not have yet developed a system to disengage, that is, voluntarily remove attention from an attended object or behavior. Similarly, it could help parents to understand that the slow and progressive development of control mechanisms during childhood 42 makes the consideration of future rewards much less likely in young children 43 .…”
Section: R E V I E Wmentioning
confidence: 99%
“…The ventral network is right lateralized and includes the temporo-parietal junction and ventral frontal cortex, whereas the dorsal network includes the frontal eye fields, intraparietal sulcus and superior parietal lobe (see Chica, Bartolomeo & Lupianez, 2013;Petersen & Posner, 2012).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%